Intraspecific ploidy variation: A hidden, minor player in plant-soil-mycorrhizal fungi interactions - Sudová, Radka; Pánková, Hana; Rydlová, Jana; Münzbergová, Zuzana; Suda, Jan (American journal of botany, 2014)
PREMISE OF THE STUDY: Genome duplication and arbuscular mycorrhizal (AM) symbiosis are ubiquitous in angiosperms. While the significance of each of these phenomena separately has been intensively studied, their interaction remains to be understood. METHODS: Three diploid and three hexaploid populations of Aster amellus (Asteraceae) were characterized in terms of the soil conditions in situ and mycorrhizal root colonization. In a greenhouse experiment, the effects of ploidy level, substrate conditions, and AM fungi on plant performance were then separated by growing noninoculated plants or plants inoculated with AM fungi in substrates native to either the diploids or hexaploids. KEY RESULTS: The diploids inhabited nutritionally richer sites but did not differ from hexaploid plants in the level of mycorrhizal root colonization in situ. In the experiment, hexaploids generally performed better than the diploids. This intercytotype growth difference was enhanced by soil fertility, with hexaploids benefiting more from nutritionally richer substrate than the diploids. AM inoculation was crucial for plant growth and phosphorus uptake. The interaction between ploidy level and AM inoculation significantly influenced only dry mass of roots, phosphorus concentrations in shoot biomass, and the length of the extraradical mycelium in the nonsterile substrates. CONCLUSIONS: Our results support the idea that polyploidy can affect the mycorrhizal growth response of host plants. Nevertheless, the effects of the interaction between ploidy and inoculation were weaker than the main effects of these factors.
Keywords: Symbiosis; Asteraceae; genome multiplication; Soil Microbiology; rhizosféra; Aster amellus; Aster Plant; mycorrhizal colonization; Aster; počet mikrobiálních kolonií; ploidie; Mycorrhizae; mycorrhizal growth response; mykorhiza; půdní mikrobiologie; symbióza; Ploidies; phosphorus uptake; Plant Shoots; Rhizosphere; Mycelium; Species Specificity; polyploidy; mycelium; Colony Count, Microbial; druhová specificita; Biomass; fosfor; výhonky rostlin; Phosphorus; arbuscular mycorrhizal symbiosis; biomasa